Application of multisegment injection on quantification of creatinine and standard addition analysis of urinary 5‐hydroxyindoleacetic acid simultaneously with creatinine normalization. Issue 3 (3rd January 2020) - Huang, Zi‐Ao; Scotland, Kymora B.; Li, Yueyang; Guo, Jian‐Ping; McGeer, Patrick L.; Lange, Dirk; Chen, David D. Y.
Abstract: In this paper, the development of a simple dilute‐and‐shoot method for quantifying urinary creatinine by CE–ESI–MS was described. The creatinine analysis time was about 7 min/sample by conventional single injection (SI) method and can be significantly reduced to less than 2 min/sample with multi‐segment injection (MSI). In addition, the standard addition analysis of 5‐hydroxyindole‐3‐acetic acid (5‐HIAA) and creatinine normalization was performed within one run by the MSI technique, and the total analysis time was 14‐min faster compared to the SI method for analyzing the same set of samples. The uses of isotopic and non‐isotopic internal standards (ISs) were compared. Creatinine‐(methyl‐ 13 C) and 5‐hydroxyindole‐4, 6, 7‐D3 ‐3‐acetic‐D2 acid (5‐HIAA‐D5 ) used as isotopic ISs can provide both accurate and precise results. In contrast, 1, 5, 5‐trimethylhydantoin (1, 5, 5‐TH) used as the non‐isotopic IS for creatinine may cause a bias of over 13% in SI method and even worse when the MSI technique was used. Another compound, 2‐methyl‐3‐indoleacetic acid (2‐MIAA), was determined not suitable for MSI analysis of 5‐HIAA due to endogenous interferences despite its acceptable performance in conventional methods of analysis.